The Influence Of Service Failure Severity On Brand Forgiveness Study On Telkomsel Users - Mulyawan, Sarah Anjani; Yudha, R. Thomas Budhyawan; Komaladewi, Rita; Kaltum, Umi (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
The aims of this study are: (1) To determine the service failure severity from internet network issues according to Telkomsel users; (2) To determine the influence of service failure severity from internet network issues on brand forgiveness of Telkomsel users; and (3) To determine the influence of service failure severity from internet network issues on each brand forgiveness dimension of telkomsel users. The study used an online survey to collect data. The sample size for this study was 100 respondents. Data analysis was conducted using mean analysis and PLS-SEM. Research Findings: The study findings indicate that: (1) the service failure severity from internet network issues, according to Telkomsel users, is categorized as high; (2) the service failure severity from internet network issues has a significant negative influence on the brand forgiveness of Telkomsel users; (3) the service failure severity from internet network issues has a significant negative influence on each brand forgiveness dimension (cognitive, affective, behavioral) of Telkomsel users. This study simplifies the research conducted by Alnawas et al. (2023) by focusing only on two main variables, service failure severity and brand forgiveness, in order to provide a more focused and in-depth understanding of the relationship between severity of service failure and brand forgiveness